Development of a Rumah Bolon-based learning trajectory to optimize student competence - Firmansyah, Firmansyah; Sari, Dwi Novita; Mujib, Abdul; Aprilia, Jelita (Universitas Jambi, Indonesia, 2026)
Indonesia, rich in culture, has great potential to implement the Merdeka curriculum integrated with culture, especially in mathematics learning. This research was conducted because field observations show that students' ability to understand culturally integrated problem-solving is not yet optimal. The aim of the study is to produce an instructional design called Rumah Bolon (HYBOL). The research approach employed is a Design Research validation study. The subjects of the study were 15 mathematics education students from Universitas Muslim Nusantara Al-Washliyah. The research instruments included HYBOL, questionnaires, and tests. The study showed that (1) the developed HYBOL is very valid, with a percentage of 93%; (2) HYBOL is very practical, with a student response score reaching 90.4%; and (3) HYBOL is effective in improving student learning outcomes, with the average score increasing from 54.5 to 86.8 and an N-Gain score of 0.72 (high category). The highest indicator achievement is the analysis of geometric transformations through Batak Gorga patterns (95.6%). It can be concluded that integrating Rumah Bolon architecture within the Realistic Mathematics Education (RME) framework can bridge the understanding of formal mathematical concepts through meaningful cultural contexts.